Correlation between the activity of Fe@ (N, S, and P) doped graphene catalysts and the coordination environment: A density functional theory study. (1st January 2023) - Chen, Manjiao; Yi, Xinqiang; Hu, Xinjun; Zhou, Xinjun; Tian, Jianping; Li, Xiulan
Abstract: Transition metal-doped graphene single-atom catalysts exhibit great application prospects for catalyzing hydrogen evolution applications. However, the precise timing and control of the activity of central atoms is a key problem to ensure the further development of catalysts. Revealing the correlation between the catalytic activity of the central atom and the coordination environment (atomic species, coordination number, and geometric configuration) is regarded as quite crucial for solving this key problem. Along these lines, in this work, Fe as the central atom and N, S, and P doped porous graphene (DPG) as the matrix material were used to systematically study the correlation between the coordination environment and the stability, catalytic activity of the catalyst. From the acquired results, it was demonstrated that: (1) The binding strength between the Fe atom and the N-atom DPG is the highest, and the anchoring strength of the Fe atom on two-element doping doped graphene is relatively low. Under the tetrad coordination condition, the catalyst doped with S and P atoms showed excellent performance in hydrogen evolution and water activation. A moderate correlation between the hydrogen evolution performance (ΔGH∗, E A, and ΔGOH∗) and d -band electronic properties ( d -CU and d -SE) under single element doping (four and three coordination) was also detected. In addition, a certain correlation between the Fe atom outer-shell electron (3d 4s) and the hydrogen evolution performance was found. A weak correlation between the electronic properties of the double element doped graphene and the hydrogen evolution performance was also confirmed from our simulations. The results are of great significance for the regulation of the single-atom catalyst activity. Graphical abstract: Image 1 Highlights: The anchoring strength of the S or P doped PG to Fe atom is lower than N-doped. The S/P doped PG with tetrad coordination showed excellent activity catalysts. The catalytic activity showed moderate correlation with d band electronic properties.